In-Vitro Antibacterial Activity of Piper Guineense Extracts and their Silver Nanoparticles Against Bacterial from Gastrointestinal Tract (London Journal of Research In Science: Natural and Formal, 2024)
The study investigates the in-vitro antibacterial activity of greenly synthesized silver nanoparticles from Piper guineeseleave (PgMLE) and seed (PgMSE) methanol extracts. The greenly synthesized silver nanoparticles from leave (PgMLEAgNPs) and seed (PgMSEAgNPs) extracts were characterized using UV-visible spectroscopy, FTIR, SEM, TEM, XRD, EDX, and TGA, and the in-vitro antibacterial activity of the extracts and nanoparticles against test pathogens from gastrointestinal tracts was evaluated.The PgMLE and PgMSE bio-reduced silver nitrate solution for the biosynthesis of PgMLEAgNPs and PgMSEAgNPs. The nanoparticles had the highest Surface plasmon resonance peaks at 500 nm. Functional groups such as alcohols, phenols, alkenes or alkynes, nitriles, ketones, aldehydes, or esters were identified as indicative of biomolecules present within PgMLEAgNPs, and PgMSEAgNPs. PgMLEAgNPs and PgMSEAgNPs were spherical flakelike and aggregated particles respectively with 15 nm in size, TEM shows the spherical shape nanoparticles. The nanoparticles were crystalline in nature and silver had the highest intensity as shown by XRD and EDX analysis. PgMLEAgNPs and PgMSEAgNPs exhibited varied antibacterial activity against the test pathogens. The antibacterial activity ranged from 2.00 to 18.00 mm in which E. coli had the highest susceptibility to PgMSEAgNPs compared to PgMLEAgNPs. The nanoparticles had better antibacterial efficacy against the test pathogens compared to the Piper guineense leaves and seed extracts. In conclusion, Piper guineense leave and seed extract nanoparticles had profound antibacterial activity against bacteria from GIT which makes them a candidate for biomedical application.
Keywords: HEA coating; DGPSAT; aging treatment; hardness; tribology properties; antibacterial activity; Piper guineensemethanol extracts; Silver nanoparticles; Gastrointestinal Tracts; Pathogens